The Effectiveness of The Integrated Population Information System (Sintren) Application In The Issuance of Death Certificates at The Population and Civil Registration Office of Cirebon Regency - Mulyana, Rico; Fajri Nurmansyah, Diky; Zulkarnaen, Iskandar; Haryo Bharoto, R. Mahendra (Asian Journal of Social and Humanities, 2024)
This study aims to determine the effectiveness of the Population Integrated Information System application program in Cirebon Regency conducted by the Population and Civil Registration Office of Cirebon Regency. This program is based on rules and regulations regulated by local and central governments, and involves various stakeholders and available resources. A qualitative approach was used in this study, with the purpose sampling method to provide an overview of the phenomena that occur. Program effectiveness based on Budiani's theory identifies four effectiveness indicators, namely target setting, program socialization, program objectives and program monitoring. The findings show that the program has been running well in the issuance of death certificates, although there are still some challenges faced, such as the lack of death certificate issuance services offered by the Population and Civil Registration Office of Cirebon Regency; second, the lack of public knowledge about the SINTREN application offered by the Population and Civil Registration Office of Cirebon Regency; and third, the Regional Apparatus Organization (OPD) is still insufficient in an effort to socialize the SINTREN application to the people of Cirebon Regency. Therefore, the study concluded that more enhanced efforts are maximizing human resources, repairing unstable networks and further socializing or educating the public to further improve the making of death certificates due to the benefits of the Death Certificate Document.